2023
DOI: 10.1158/2326-6066.cir-22-0658
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Promotes the Immunosuppressive Activity of MDSCs in Colorectal Cancer

Abstract: Myeloid-derived suppressive cells (MDSCs) inhibit antitumor immunity and confer a survival advantage for tumor evasion. Tumor cells also support MDSC expansion and recruitment by secreting multiple growth factors and cytokines, but the mechanisms by which tumors affect MDSC function are not completely understood. Here, we found that the neuronal guidance protein netrin-1 was selectively secreted by MC38 murine colon cancer cells, which could enhance the immunosuppressive activity of MDSCs. MDSCs predominantly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, MDSCs are known to express ectonucleotidases that contribute to the formation of adenosine in a HIF-1α dependent pathway [80]. Moreover, very recently, netrin-1 was shown to increase the suppressive activity of MDSC [81], so that decreased netrin-1 levels in Hif1a loxP/loxP LysM Cre+ mice could potentially have an effect on MDSC functionality. However, these considerations are pure speculation here and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MDSCs are known to express ectonucleotidases that contribute to the formation of adenosine in a HIF-1α dependent pathway [80]. Moreover, very recently, netrin-1 was shown to increase the suppressive activity of MDSC [81], so that decreased netrin-1 levels in Hif1a loxP/loxP LysM Cre+ mice could potentially have an effect on MDSC functionality. However, these considerations are pure speculation here and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 113 NTN1 knockdown in tumour cells decreased the immunosuppressive activity of myeloid‐derived suppressive cells (MDSCs) and restored antitumor immunity in MC38 tumour xenograft mice, according to Xia et al. 116 The molecular mechanism investigation revealed that NTN1 significantly enhanced the immunosuppressive function of MDSCs through A2BR on MDSCs, thus promoting the development of tumours. In addition, Ducarouge et al.…”
Section: The Vital Roles and Mechanism Of Netrins In Cancer Diagnosis...mentioning
confidence: 94%
“…Pten f/f EC mice treated with NP137 had an increase in CD8 + cells. 113 NTN1 knockdown in tumour cells decreased the immunosuppressive activity of myeloid-derived suppressive cells (MDSCs) and restored antitumor immunity in MC38 tumour xenograft mice, according to Xia et al 116 The molecular mechanism investigation revealed that NTN1 significantly enhanced the immunosuppressive function of MDSCs through A2BR on MDSCs, thus promoting the development of tumours. In addition, Ducarouge et al 117 discovered that NTN1 interference limits tumour resistance to immune checkpoint inhibitors and provided evidence linking this enhanced anti-tumour efficacy to a decreased recruitment of a subtype of MDSCs called polymorphonuclear (PMN)-MDSCs.…”
Section: The Vital Role S and Mechanis M Of Ne Trin S In C An Cer D I...mentioning
confidence: 98%
“…Studies have proven that excessive amounts of circulating MDSCs are closely related to poor prognosis, tumor angiogenesis, and tumor evasion immunity [ 4 ]. This reveals a new regulatory mechanism of tumor growth and provides a new research direction for tumor therapy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%